Altered Microstate Dynamics and Spatial Complexity in Late-Life Schizophrenia - Lin, Gaohong; Wu, Zhangying; Chen, Ben; Zhang, Min; Wang, Qiang; Liu, Meiling; Zhang, Si; Yang, Mingfeng; Ning, Yuping; Zhong, Xiaomei (Frontiers in Psychiatry, 2022)
Abstract Background: Resting-state EEG microstate and omega complexity analyses have been widely used to explore deviant brain function in various neuropsychiatric disorders. This study aimed to investigate the features of microstate dynamics and spatial complexity in patients with late-life schizophrenia (LLS). Method: Microstate and omega complexity analyses were performed on resting-state EEG data from 39 inpatients with LLS and compared with 40 elderly normal controls (NCs). Result: The duration of microstate classes A and D were significantly higher in patients with LLS compared with NCs. The occurrence of microstate classes A, B, and C was significantly lower in patients with LLS compared with NCs. LLS patients have a lower time coverage of microstate class A and a higher time coverage of class D than NCs. Transition probabilities from microstate class A to B and from class A to C were significantly lower in patients with LLS compared with NCs. Transition probabilities between microstate class B and D were significantly higher in patients with LLS compared with NCs. Global omega complexity and anterior omega complexity were significantly higher in patients with LLS compared with NCs. Conclusion: This study revealed an altered pattern of microstate dynamics and omega complexity in patients with LLS. This may reflect the disturbed neural basis underlying LLS and enhance the understanding of the pathophysiology of LLS.